Intertidal Oyster Reef Mapping and Population Analysis in West Galveston Bay, Texas - Marc H. Hanke; Amanda Hackney; Susan A. Heath (Ecologies)
Intertidal reefs comprised of the eastern oyster (Crassostrea virginica) are an important habitat type within the estuarine landscape and provide many unique ecosystem services. Within West Galveston Bay (WGB), Texas, this type of reef plays an important ecological role; however, the system’s intertidal reef abundance, structure, and habitat provisions are relatively understudied, and the current spatial extent of these reefs has not been recently quantified. The primary objectives of the study were to identify intertidal oyster reefs utilizing GIS models and sample representative reefs for topographical characteristics, oyster demographics, and the associated benthic macrofauna (ABM) community composition in WGB from August 2019 to February 2020. Secondarily, GIS models and oyster population abundance were utilized to estimate the intertidal oyster abundance in WBG. The total area of intertidal oyster reefs in WGB was estimated to be 818,128 m2, with 59,931 m2 of reefs confirmed through GIS analysis and ground truthing, and the GIS model estimating an additional 758,197 m2 of reef. Through ground truthing, reefs were found to be either shell rakes, consisting of piled shell with minimal three-dimensional structure and oysters, or true intertidal reefs with high reef structure and oyster abundance. High oyster abundance was spatially distributed within the northeastern and southwestern areas of WGB and the total intertidal oyster population, coupling the GIS models and reef sampling, was estimated to be 500 million individual oysters. The ABM community was sparse in terms of richness and diversity, further indicating a lack of structural complexity in most of the reefs within this system. This study demonstrates the importance of coupling field results with GIS modeling to estimate system level population sizes and furthers the understanding of the spatial distributions of intertidal oyster reef to promote management, conservation, and restoration efforts.